Geology, Petrography and Structural analysis of Jada area, Northeastern Nigeria - Ahmed, H. A.; Halilu, M.; Salisu, I. A.; Vandi, D. K. (IJRDO-Journal of Applied Science, 2017)
The study area, forms part of the Hawal massive regarded as an extension of Bamenda massivethat forms part of the Cameroun volcanic line in the Northeastern part of Nigeria (Ekwueme1993). Eighteen samples collected in the study area were used for petrographic analyses inaddition to the geological field mapping and structural analysis. The hand specimen descriptionsand results of microscopic studies of the collected samples in the area revealed that quartz,feldspar and biotite are the predominant minerals in the rocks exposed, which are mainlygranites, gneisses, diorites. Field relations and petrographic analysis suggest the occurrence ofalkaline rocks in the study area and series of thermo-tectonic activities that resulted intonumerous structural features and emplacement of different rock units that might have significantresource potentials.